MARKETING STRATEGIES IN IMPROVING THE PERFORMANCE OF CULINARY MSMES: A SYSTEMATIC LITERATURE REVIEW - Liva Maulidya; Rusni Azhary Safitri; Putri Amelia; Elda Riska (BEMJ: Business, Entrepreneurship, and Management Journal, 2026)
Abstract This study examines the role of marketing strategies in improving the performance of culinary MSMEs using a Systematic Literature Review approach. Scientific publications from 2020–2025 were collected through Publish or Perish and Google Scholar and analyzed using bibliometric methods and TF-IDF–based text mining. The findings indicate that marketing strategies, particularly digital marketing, marketing innovation, and market orientation, significantly enhance MSME competitiveness and performance. However, research linking marketing strategies to long-term business sustainability remains limited. This study provides a conceptual foundation for developing adaptive and sustainable marketing strategies for culinary MSMEs. Keywords: Marketing Strategy, Culinary MSMEs, MSME Performance, Digital Marketing, Systematic Literature Review